2020
DOI: 10.1371/journal.pone.0241887
|View full text |Cite
|
Sign up to set email alerts
|

Comparing three screen-based sedentary behaviours’ effect upon adolescents’ participation in physical activity: The ESSENS study

Abstract: Background Literature focusing on the association between sedentary behaviours and physical activity has provided equivocal results and has been dominated by TV viewing as the indicator of sedentary behaviour. There is a need for more studies exploring the association between contemporary screen activities and physical activity among youth. Methods A cross-sectional study including 742 adolescents was conducted in 2016. Data were collected at school through an online questionnaire. Regression analyses were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
4
1
1
Order By: Relevance
“…The present study indicates that the most sedentary behaviour carried out by children was screen-based activities such as watching television or videos, playing smartphones or online games, tablets, or computers [24]. Previous research has also shown that school-age children most frequently do screen-based activities, but this research was conducted before the COVID-19 pandemic, which was at least 1 hour/day and increased on holidays, which was 2 hours/day [25].…”
Section: Discussionmentioning
confidence: 58%
“…The present study indicates that the most sedentary behaviour carried out by children was screen-based activities such as watching television or videos, playing smartphones or online games, tablets, or computers [24]. Previous research has also shown that school-age children most frequently do screen-based activities, but this research was conducted before the COVID-19 pandemic, which was at least 1 hour/day and increased on holidays, which was 2 hours/day [25].…”
Section: Discussionmentioning
confidence: 58%
“…From studies in our literature pool that explored passive viewing ST, almost all showed unfavourable associations with a variety of physiological, psychological, and educational outcomes for the users, including sleep and physical health, physical activity, psychological well-being, social communication, and academic achievement ( Arora et al, 2018 ; Arora et al, 2014 ; Berentzen et al, 2014 ; Chortatos, et al, 2020 ; Engberg et al, 2020 ; Falbe et al, 2013 ; Gebremariam et al, 2013 ; Lane et al, 2014 ; Melkevik et al, 2010 ; Nagata et al, 2021 ; Przybylski & Weinstein, 2017 ; Sanders et al, 2019 ; Yang et al, 2020 ). This supports findings from prior systematic literature reviews and meta-analyses ( Adelantado-Renau et al, 2019 ; Fang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to gaming ST, some studies found unfavourable associations with health-related and psychological well-being indicators including trouble with sleep, obesity, poor dietary choices, peer problems, physical activity and poor mental health among others ( Arora et al, 2018 ; Arora et al, 2014 ; Chortatos, et al, 2020 ; Falbe et al, 2013 ; Gebremariam et al, 2013 ; Janssen et al, 2012 ; Lange et al, 2017 ; Melkevik et al, 2010 ; Phan et al, 2019 ; Przybylski & Weinstein, 2017 ; Rosen et al, 2014 ; Sanders et al, 2019 ). On the contrary, one study found a small positive association between gaming ST's associations and educational outcomes ( Sanders et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…El sedentarismo y la actividad física son dos variables independientes y no excluyentes entre sí, de modo que un adolescente puede cumplir las recomendaciones de actividad física y dedicar más de dos horas diarias a las pantallas en su tiempo de ocio (92,299,300). No obstante, algunos estudios exponen una relación inversa entre la actividad física y el tiempo de pantalla, aunque en ocasiones sin tener en cuenta otras covariables (301,302).…”
Section: Actividad Física En El Transporteunclassified